Multiple cerebral hydatidosis - Genolet, Christian; Giménez, Maximiliano; Piatti, Giuliano; Rivamar, Gabriel; Schiro, Marcos; Couto, Juan Pablo (Revista Argentina de Neurocirugía, 2025)
Background: hydatidosis is a zoonosis caused by the parasite Echinococcus granulosus, with a high prevalence in various regions of the world. The main organs affected are the liver and lungs, with cerebral localization being rare, representing only 2% of cases. Objectives: to describe a case of multiple cerebral hydatidosis and analyze the published literature. Case description: we present the case of a 16-year-old male patient from a rural area with headache, hemiparesis, and difficulty walking for 3 months. Imaging studies revealed multiple bilateral cerebral cysts, as well as cardiac, renal, pancreatic, and muscle cysts. The diagnosis of hydatidosis was based on imaging studies, serological tests, and pathological anatomy. Surgery: six cerebral cysts were surgically removed using the Dowling technique. The patient recovered without complications, and albendazole treatment continued postoperatively. Conclusion: multiple cerebral hydatidosis without liver or lung involvement is an extremely rare presentation. Early diagnosis and a multidisciplinary approach, including medical and surgical treatment, are essential for the successful management of this condition.